Differential effects of fine particulate matter constituents on acute coronary syndrome onset - Yixuan Jiang; Chuyuan Du; Renjie Chen; Jialu Hu; Xinlei Zhu; Xiaowei Xue; Qinglin He; Jun Lu; Junbo Ge; Yong Huo; Haidong Kan (Nature Communications)
Abstract Fine particulate matter has been linked with acute coronary syndrome. Nevertheless, the key constituents remain unclear. Here, we conduct a nationwide case-crossover study in China during 2015–2021 to quantify the associations between fine particulate matter constituents (organic matter, black carbon, nitrate, sulfate, and ammonium) and acute coronary syndrome, and to identify the critical contributors. Our findings reveal all five constituents are significantly associated with acute coronary syndrome onset. The magnitude of associations peaks on the concurrent day, attenuates thereafter, and becomes null at lag 2 day. The largest effects are observed for organic matter and black carbon, with each interquartile range increase in their concentrations corresponding to 2.15% and 2.03% increases in acute coronary syndrome onset, respectively. These two components also contribute most to the joint effects, accounting for 31% and 22%, respectively. Our findings highlight tailored clinical management and targeted control of carbonaceous components to protect cardiovascular health.